Developing Brief Opportunistic Interactions: practitioners facilitate patients to identify and change health risk behaviours at an early preventive stage. Issue 4 (20th November 2015) - Docherty, Barbara; Sheridan, Nicolette; Kenealy, Timothy
Abstract : Aim: To identify shortcomings in existing models of patient behaviour change, and present the development and testing of a novel approach using practitioner facilitation and person-focussed conversations that identifies and addresses behaviours at an earlier stage than current models. Background: Systematic strategies used by health professionals to change patient behaviours began with motivational interviewing and brief intervention approaches for serious addictive behaviours. Practitioners typically presume they should drive the process of patient behaviour change. Attempts to transfer these approaches to primary care, and a broader range of health risk behaviours, have been less successful. The TADS programme (Tobacco, Alcohol and Other Drugs, later Training and Development Services) began teaching motivational interviewing and brief interventions to practitioners in New Zealand in 1996. Formal and informal evaluations showed that practitioners used screening tools that patients rejected and that led to incomplete disclosure, used language that did not engage patients, failed to identify the behaviours patients wished to address and therefore misdirected interventions. Methods: Iterative development of new tools with input from patients and primary care clinicians. Findings: The TADS programme developed a questionnaire whose results remained private to the patient, which enabled the patient to identify personal behaviours that they might choose to change (the TADS Personal Assessment Choice Tool). This was assisted by a brief conversation that facilitated and supported any change prioritised by the patient (the TADS Brief Opportunistic Interaction). The need for this approach, and its effectiveness, appeared to be similar across adults, youth, different ethnic groups and people in different socio-economic circumstances. Behaviours patients identified were often linked to other health risk behaviours or early-stage mental health disorders that were not easily detected by practitioner-driven screening or inquiry. The long-term effectiveness of this approach in different populations in primary health care settings requires further evaluation.